THE IMPORTANCE OF ACTIVATING THE TECHNICAL BURIAL CENTERS FOR WASTE TO PRESERVE THE ENVIRONMENT AND ELIMINATE THE CRISIS OF RANDOM DUMPS: CONSTANTINE’S CASE - Mohamed, Trifa; Khedija, Selami; Tahar, Messaoudi (The journal of contemporary issues in business and government, 2023)
The projects of technical burial centers for waste, conversion units, sorting and passive dumps are of great importance and the only solution in the absence of parallel projects, or in the process of establishing them, such as the waste valuation project for the innovative project in partnership with the United Nations Development Program, which provides goals that are capable of providing and creating jobs In line with the principles of sustainable development, strengthening the circular economy, bringing financial returns and combating climate variables and global warming, by involving citizens and associations in the management and setting a budget of its own to finance it with sufficient space that would solve the Constantine crisis represented by the phenomenon of random hollows and the creation of wealth and work positions in the light of preserving The environment, by activating this project, which can eliminate the problem of waste that littered the state of Constantine in particular, and it helps that a very large amount of organic waste can be evaluated and recycled, and this is a positive thing for the state.